A VIEW ON AN EDGE PAIR SUM GRAPHS (International Journal of Food and Nutritional Sciences, 2022)
A graph with an edge pair sum labeling is called an edge pair sum graphs. In this paper we prove that edge pair sum graphs. A graph which admits edge pair sum labeling is called an edge pair sum graphs. The origin of graph theory started with the problem of Konigsberg bridge in 1735.